The influence of the coefficient of variation on the process reliability of brick production - Pakhomova Ekaterina Gennadievna (Institut za istrazivanja i projektovanja u privredi, 2021)
The goal of research was studying the influence of the variation coefficient values during statistical tests of building structures on the destruction probability and reliability of brick building structures. The article focuses on comparing the theoretical values of the probability theory problems with their practical application in building structures behavior calculation. The scientific novelty lies in the comparison of the calculated data according to the normal distribution with the practical values of the experiment carried out on brick structures. As a result, a dependence graph dependence of the reliability coefficient k on the brick grade was, taking into account various coefficients of variation.